Pedagogy, printing, and Protestantism : the discourse on childhood - Luke, Carmen (State University of New York Press, 1989)
Annotation. Examines current methods and promising new techniques for assessing and managing pain in infants, children, and adolescents. An international group of clinicians, nurses, and researchers highlight recent achievements in designing tools for measuring pain in children and developing pharmacological and behavioral strategies for controlling acute pain, chronic nonmalignant pain, and cancer pain. Luke applies Foucault's method of discursive analysis to the history of childhood, in this case in 16th century Germany, and argues that Martin Luther's call for public schools to promote the literacy necessary for the new theology, and the contemporaneous development of the printing press, led to a widespread reconceptualization of childhood and education. Paperback edition ($12.95) not seen. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Education -- Germany -- History -- 16th century.; Child rearing -- Germany -- History -- 16th century.; Printing -- Germany -- History -- 16th century.; Printing -- Social aspects -- Germany.; Protestant churches -- Germany -- History -- 16th century.; Reformation -- Germany.; Germany -- Church history -- 16th century.; Technology and civilization.; Éducation des enfants -- Allemagne -- Histoire -- 16e siècle.; Imprimerie -- Allemagne -- Histoire -- 16e siècle.; Imprimerie -- Aspect social -- Allemagne.; Églises protestantes -- Allemagne -- Histoire -- 16e siècle.; Réforme (Christianisme) -- Allemagne.; Technologie et civilisation.; Éducation -- Allemagne -- Histoire -- 16e siècle.; Allemagne -- Histoire religieuse -- 16e siècle.; EDUCATION -- History.; EDUCATION -- Comparative.; Child rearing; Education; Printing; Printing -- Social aspects; Protestant churches; Reformation; Technology and civilization; Germany; Erziehung; Buchdruck; Pädagogik; Protestantismus; Druckwerk; Kind; Deutschland; Pedagogiek.; Boekdrukkunst.; Reformatie.; 1500-1599; Geschichte 1500-1600.; Geschichte 1480-1550.; Church history; History